Difference of zinc volatility in diverse carrier minerals: The critical limit of blast furnace dust recycle. (15th January 2018) - Hu, Wen-tao; Xia, Han-wen; Pan, Dong-ling; Wei, Xin-lei; Li, Jia; Dai, Xiao-jie; Yang, Feihua; Lu, Xin; Wang, Hua-jun
Highlights: The critical limits of Zn and Pb volatilization have been found. The volatility of Zn and Pb is depends on its carrier minerals. The volatilizing resistance from carbon is enhanced by the increase of coke dosage. The volatiles obtained can be used directly without purification. Abstract: Blast furnace dust is a typical secondary resource produced in manufacturing iron. This substance contains many recyclable components, such as iron, lead, zinc, and carbon, which have not been properly utilized. Zinc is a dispersed component in blast furnace dust, but its volatility depends on its carrier minerals, such as hematite, coke, and silicate in descending order of zinc volatility. Volatilization is the necessary procedure of removing toxicity and recycling zinc from blast furnace dust. However, two critical limits exist: the amount of carbon in the residue and the amount of franklinite in the blast furnace dust. Zinc can be enclosed by the carbon grains according to kinetic analysis and energy dispersive spectrometer (EDS) tests. Therefore, the coke dosage should be controlled carefully to avoid carbon residue and increase the volatilization rate of zinc. Meanwhile, both franklinite and zincite are general zinc-bearing phases in the adopted dust, but neither can volatilize before being reduced to metallic form. Calculations show that the available reduction temperature of zincite is higher than that of franklinite. Nearly all the zinc in hematite and carbon is in the form of zincite and can be easily reduced in the heating process. However, the zinc in silicate mainly exists in the form of franklinite and is difficult to be reduced and volatilized, which explains the lower volatilization rate of zinc in silicate than in coke and hematite. In the last part of this investigation, the mineral phase and morphology of the volatiles obtained after fume reduction volatilization are tested for the first time to evaluate their potential application value. Only high-purity crystal zincite is found, which means that the volatiles can be used directly as high-grade zinc smelting materials without purification.